Experimental Analysis of Electric Discharge Machining Over Inconel 825 Using Copper Electrode and Al2O3 Coated Copper Electrode - Rajamanickam, S; Manjunathan, R; Palani, R; Peer Mohamed, J; Monesh, D; Aakash, A (International Journal of Engineering and Technology, 2018)
In this project work, Electric Discharge Machining (EDM) of Inconel 825 is done with a copper electrode and Al2O3 coated copper electrode. The objective of this paper is to reduce the tool wear by employing Al2O3 coated copper electrode. And also the optimum combination of machining parameters had been arrived using grey relational analysis. It is concluded that the voltage of 25 v, a peak current of 15 A, pulse on-time of 30 Î¼s, pulse off-time of 9 Î¼s provides optimum solutions. The Inconel 825 is one of the hardest materials and finds wide applications in high-tech industries due to its sole advantages.Â Â